2016
DOI: 10.1177/0300985816650243
|View full text |Cite
|
Sign up to set email alerts
|

Feline Mammary Cancer

Abstract: Feline mammary carcinoma (FMC) is similar to human breast cancer in the late age of onset, incidence, histopathologic features, biological behavior, and pattern of metastasis. Therefore, FMC has been proposed as a relevant model for aggressive human breast cancer. The goals of this study were to develop a nude mouse model of FMC tumor growth and metastasis and to measure the expression of genes responsible for lymphangiogenesis, angiogenesis, tumor progression, and lymph node metastasis in FMC tissues and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 58 publications
(84 reference statements)
0
30
1
Order By: Relevance
“…MYL10, ACTB, RAC1, and MYLPF) involved in cell movement, actin cytoskeleton remodelling, and cellular proliferation and motion such as SBDS, ITGAM, PDGFA, and RAC1. Among them, RAC1 actively promotes cell motility in breast cancer cells 64,65 and PDGFA has been reported as highly expressed in FMCs and derived cell lines 66 . Furthermore, E3 1.1-34.5 Mb harboured SERPINE1; a gene encoding a cell adhesion protein involved in invasion and metastasis promotion in different human malignancies including HBCs [67][68][69] Analysis of common CNLs significantly correlated with reduced survival intervals.…”
Section: Analysis Of Common Cngs Significantly Correlated With Reducementioning
confidence: 99%
“…MYL10, ACTB, RAC1, and MYLPF) involved in cell movement, actin cytoskeleton remodelling, and cellular proliferation and motion such as SBDS, ITGAM, PDGFA, and RAC1. Among them, RAC1 actively promotes cell motility in breast cancer cells 64,65 and PDGFA has been reported as highly expressed in FMCs and derived cell lines 66 . Furthermore, E3 1.1-34.5 Mb harboured SERPINE1; a gene encoding a cell adhesion protein involved in invasion and metastasis promotion in different human malignancies including HBCs [67][68][69] Analysis of common CNLs significantly correlated with reduced survival intervals.…”
Section: Analysis Of Common Cngs Significantly Correlated With Reducementioning
confidence: 99%
“…Due to the similarities between human breast cancer and feline mammary carcinoma [ 6 – 10 ], new clinical studies on FMC may identify novel diagnostic markers and therapeutic targets that can probably be used in human patients. Recently, it was demonstrated that stroma cells of breast tumors synthesize the chemokine SDF-1, which via its cognate receptor (CXCR4) supports tumor growth through autocrine and paracrine mechanisms [ 14 , 19 , 24 , 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The feline mammary carcinoma (FMC) is very common in cat (12-40% of all neoplasms), showing overexpression of the HER2 protooncogene in 33%-60% of the cases [ 1 – 5 ]. Sharing phenotypic and genotypic similarities with human breast tumor [ 6 – 10 ], spontaneous FMCs can also be classified in the same subtypes (luminal A, luminal B, luminal B-like, epidermal growth factor receptor type II-positive and triple negative) [ 7 , 11 ], being considered a suitable model for breast cancer studies.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, these clinical trials with dog patients suffering from spontaneously occurring tumors would provide insights for a possible translation of this approach back to human oncology, or to other species, like cats, that are also heavily affected by EGFR-overexpressing malignancies [ 29 ]. Also here, this novel theranostic approach could exploit imaging options in order to select patients more effectively.…”
Section: Discussionmentioning
confidence: 99%